Kemampuan Berpikir Kritis dan Kreatif Matematis Siswa SMP Melalui Pembelajaran Berbasis Masalah dengan Strategi Konflik Kognitif - Ismaimuza, Dasa (Sains Humanika, 2013)
Students’ creative thinking ability on mathematics is an important component that must be owned by a student as these abilities having this will help students in solving mathematical problems, including everyday problems. Problem-based learning combined with cognitive conflict strategy (PBLKK) can be implemented for developing this ability. PBLKK is a contrasting students’ learning cognitive structure. In this situation there is a conflict between the knowledge possessed by the students and the situation which has been provided. The main problem in this research is how junior high school students’ creative thinking ability on mathematics student’s VIII. This research is experimental research. The population in this study is junior high shool students in the city of Palu. The sample is 200 students in SMPN 1, SMPN 6, and SMPN 18. The instruments used in this study include mathematics test, students’ records, test of mathematical skills in creative thinking. Data analysis in hypothesis testing used t-test, one-way Anova, two-way Anova test. Based on the results and analysis of research data, it is found that: (1) Students’ creative thinking ability on mathematics who have received PBLKK better than these of students who received conventional learning (KV); (2) There are differences in terms of students’ creative thinking ability on mathematics based on school levels and students’ prior knowledge; (3) There is no interaction between school levels and learning models on critical and creative thinking ability on mathematics and students’ attitudes; (4) There is no interaction between students’ prior knowledge and learning models on critical and creative thinking ability on mathematics as well as students’ attitudes.